MENELAAH SAFAR DALAM PSIKOLOGI ISLAM - Subhan Subhan (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2020)
This article discusses the concept of safar in the perspective of Islamic psychology which has not been widely studied scientifically. Safar is usually more interpreted as a mere physical journey, without any attempt to cultivate psychological values cum spiritual. For this reason, the author explores safar based on the sufi point of view of Imam Al-Ghazali. The method in this research uses two approaches: literature study written by Imam al-Ghazali and empirical data mining by interviewing doctoral students of Islamic psychology study program at Muhammadiyah University of Yogyakarta. Some of the findings in this research include: safar is very beneficial for the psyche of a person who is a traveler, even when the traveler is experiencing obstacles in his safar.